Production of Liquid Organic Fertilizer from Various Organic Waste Sources for Vegetable Cultivation in Bulotalangi Timur Village, Gorontalo - Yusrina, Safira Zahrah; Putra, Muhammad Rafli Ariq; Saragih, Davina Patricia; Damanik, Ruth Shinta; Sinambela, Ester; Lahusin, Azwar; Sumiahadi, Ade (Indonesian Journal of Community Services Cel, 2025)
Background: Bulotalangi Timur Village is dominated by vegetable farmers who rely heavily on chemical fertilizers, making them vulnerable to fertilizer shortages that can negatively affect crop productivity. Although organic fertilizers derived from organic waste offer a sustainable alternative, farmers’ knowledge and skills regarding their production and application remain limited.Aims: This activity aimed to improve farmers’ knowledge and skills in producing liquid organic fertilizer (LOF) from organic waste as an environmentally friendly approach to enhance crop productivity and support sustainable village development.Method: The activity was conducted in Bulotalangi Timur Village, Bulango Timur District, Bone Bolango Regency, Gorontalo Province, in October 2023. It consisted of three stages: planning, implementation, and evaluation. The implementation employed training methods that combined socialization and participatory demonstrations to facilitate hands-on learning.Results: The training program was implemented smoothly and received a very positive response from participants, as indicated by their high level of enthusiasm and satisfaction. Participants expressed a strong expectation for the continuation of similar activities in the future. However, several challenges were identified, including limited initial awareness of organic waste utilization and scheduling constraints that led to relatively low participation rates.